2022
DOI: 10.3889/oamjms.2022.8424
|View full text |Cite
|
Sign up to set email alerts
|

Underweight, Stunted, and Wasted among Children with Congenital Heart Disease: Acyanotic versus Cyanotic

Abstract: BACKGROUND Congenital heart disease (CHD) is the most common of all congenital lesions and is the most common type of heart diseases among children. Children with congenital heart disease are at increased risk of underweight, stunted and wasted. Wasted is a reflection of acute malnutrition, stunted is a reflection of chronic malnutrition while underweight is a reflection of both. OBJECTIVE To describe the prevalence of underweight, stunted and wasted among children with acyanotic and cyanotic CHD, in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…In addition to being severely underweight, children with cyanotic CHD also tended to suffer from stunting, whereas children with acyanotic CHD were more likely to have a normal length or height-for-age curve. These results were in accordance with the findings of a previous investigation conducted at Sanglah Hospital, Denpasar, Indonesia, which suggested a higher prevalence of stunting in cyanotic CHD compared to acyanotic CHD groups [ 17 ]. The cause of stunting in children with CHD has been linked to chronic hypoxia that possesses a direct or indirect effect on decreasing the insulin-like growth factor I (IGF-I) hormone [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to being severely underweight, children with cyanotic CHD also tended to suffer from stunting, whereas children with acyanotic CHD were more likely to have a normal length or height-for-age curve. These results were in accordance with the findings of a previous investigation conducted at Sanglah Hospital, Denpasar, Indonesia, which suggested a higher prevalence of stunting in cyanotic CHD compared to acyanotic CHD groups [ 17 ]. The cause of stunting in children with CHD has been linked to chronic hypoxia that possesses a direct or indirect effect on decreasing the insulin-like growth factor I (IGF-I) hormone [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…The disruption of the IGF-I mechanism will affect bone growth in children. Children with cyanotic CHD often present with abnormal length/height [ 17 ]. In addition, a lack of nutritional intake, high energy needs, and pulmonary hypertension are among other suggested factors influencing the incidence of growth failure in children with CHD [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, delays in language and gross motor development occurred more often in CCHD children than in normal children. These ndings were in line with the 3 Indonesia studies by Maya et al 20207 , Amelia et al 202033 , and Agustini et al 202234 . Similarly, Aghaei-Moghadam et al 2019 in Iran35 reported consistent results in this study.…”
supporting
confidence: 90%
“…Hal ini disebabkan anak dengan PJB berisiko untuk terjadi penurunan asupan gizi dan peningkatan kebutuhan energi. Pada anak dengan PJB yang mengalami gagal jantung, terjadi peningkatan pengeluaran energi akibat kerja jantung yang bekerja lebih keras dalam memompa darah untuk metabolisme tubuh [16]. Kondisi PJB juga menyebabkan anak mengalami peningkatan konsumsi oksigen, peningkatan aktivitas saraf simpatis, sampai dengan kesulitan pemberian makan [17].…”
Section: Hasilunclassified